(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2026)
For most traditional banks, lending activity remains the major source of revenue. However, there is always a possibility that some borrowers default on their loans and this situation creates credit risk for banks. To manage this risk, banks utilize different qualitative and quantitative methods to predict loan defaults. Currently, traditional algorithms such as logistic regression and decision trees are among the most popular models used to predict loan defaults. Their simple implementation and high accuracy make them preferred choice among credit analysts. However, rapid technological progress and increased computing capabilities of computers are creating opportunities to apply more advanced machine learning algorithms for managing credit risk. For instance, deep neural networks and recently developed Extreme Gradient Boosting algorithms (XGB) have been shown to exhibit high accuracy in wide range of classification tasks and have potential to exhibit high accuracy in loan default prediction.